PENGARUH EDUKASI PERAWAT TERHADAP KETEPATAN KELUARGA PASIEN MELAKUKAN CUCI TANGAN DALAM PENCEGAHAN PENULARAN COVID-19 DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Nurul Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Corona virus is a virus that attacks the respiratory system. The high incidence of Covid-19 is due to low public awareness of applying health protocols. So the need for prevention and control efforts by complying with health protocols to wear masks, keep your distance and wash your hands properly. Washing hands is an easy routine and is important in infection control, and is the best method to prevent the transmission of microorganisms. The purpose of this study was to determine the effect of nurse education on the accuracy of the patient's family through hand washing in preventing Covid-19 transmission at Arifin Achmad Hospital, Riau Province. This research uses quantitative research with a quasi experimental design, with a population of 20 people. Data collection tools used observation sheets and data analysis was carried out univariate and bivariate with the Wilcoxson test. The results of this study show that the average value before being given education about hand washing is low compared to the average value after being given education about hand washing. So that hand washing education is effective in increasing hand washing to prevent Covid-19 transmission with a p-value of 0.000. The results of this study are expected to be a source of information and knowledge for the nursing profession regarding the effect of providing nurse education on the accuracy of the patient's family in washing hands.